Hazards and Risk Assessment for Physical Hydraulic Structures of Dam Model in the Laboratory - Wiyono Wit Saputra, Anggara; Rubiantoro, Prasetyo; Tri Juwono, Pitojo; Harisuseno, Donny; Sidqi Fidari, Jadfan (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2024)
Some workers often neglected Occupational Health and Safety (OHS) regulations in the laboratory environment, resulting in potential hazards that ultimately led to workplace accidents. The physical hydraulic model of dam structures in this laboratory involved activities that posed potential risks. Hazard assessment and the risk of workplace accidents were identified through direct field observations to pinpoint potential risks associated with these activities. Questionnaires and interviews with personnel involved in laboratory activities, including workers and technicians, were conducted to gather relevant data concerning the research problem. This study aimed to identify potential risks and hazards using a Job Safety Analysis approach and to assess the risks associated with each activity stage. Risk levels at various stages of work were determined through job safety analysis within the OHS management system. Risk identification encompassed impacts on individuals, equipment, materials, and the environment. The highest high-risk and moderate-risk identified from the assessment are the demolition of the previous dam model in the site preparation step and the preparation of the electric water pump with a capacity of 100 l/second in the running stage. Generally, based on the identified risk categories, risk mitigation for dam model testing work in the laboratory included using Personal Protective Equipment (PPE) such as ear protection, masks, helmets, safety shoes, and gloves to prevent work-related accidents.